Roadmap on electromagnetic metamaterials and metasurfaces - Cui, Tie Jun; Zhang, Shuang; Alu, Andrea; Wegener, Martin; Pendry, John; Luo, Jie; Lai, Yun; Wang, Zuojia; Lin, Xiao; Chen, Hongsheng; Chen, Ping; Wu, Rui-Xin; et al. (Journal of Physics: Photonics)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

An alternative and robust formulation of the fatigue crack growth rate curve for long cracks - Kullmer, Gunter; Weiß, Deborah; Schramm, Britta (Engineering Fracture Mechanics)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Multiscale simulation of polymer curing of composites combined mean-field homogenisation methods at large strains - Lenz, Peter; Mahnken, Rolf (International Journal of Solids and Structures)
Keywords: Applied Mathematics; Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science; Modeling and Simulation

Insights into the First Multi-Transition-Metal Containing Ruddlesden Popper-Type Cathode for all-solid-state Fluoride Ion Batteries - Vanita, Vanita; Waidha, Aamir Iqbal; Vasala, Sami; Puphal, Pascal; Schoch, Roland; Glatzel, Pieter; Bauer, Matthias; Clemens, Oliver (Journal of Materials Chemistry A)
Promising cathode materials for fluoride-ion batteries (FIBs) are 3d transition metal containing oxides with Ruddlesden-Popper-type structure. So far, multi-elemental compositions were not investigated, but could alternate electrochemical performance similar to what has been found for cathode materials for lithium-ion batteries. Within this study, we investigate RP type La2Ni0.75Co0.25O4.08 as an intercalation-based active cathode material for all-solid-state FIBs. We determine the structural changes of La2Ni0.75Co0.25O4.08 during fluoride intercalation / de-intercalation by ex-situ X-ray diffraction, which showed that F- insertion leads to transformation of the parent phase to three different phases. Changes in Ni and Co oxidation states and coordination environment were examined by X-ray absorption spectroscopy and magnetic measurements in order to understand the complex reaction behaviour of the phases in detail, showing that the two transition metals behave differently in the charging and discharging process. Under optimized operating conditions, a cycle life of 120 cycles at a critical cut-off capacity of 40 mAh g-1 against Pb/PbF2 was obtained, which is one of the highest observed for intercalation electrode materials in FIBs so far. The average Coulombic efficiencies ranged from 85% to 90%. Thus, La2Ni0.75Co0.25O4.08 could be a promising candidate for cycling-stable high-energy cathode materials for all-solid-state FIBs
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Dynamics of Electron–Hole Coulomb Attractive Energy and Dipole Moment of Hot Excitons in Donor–Acceptor Polymers - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Influences of Weld Nugget Shape and Material Gradient on the Shear Strength of Resistance Spot‐Welded Joints - Schuster, Lilia; Olfert, Viktoria; Sherepenko, Oleksii; Fehrenbach, Clemens; Song, Shiyuan; Hein, David; Meschut, Gerson; Biro, Elliot; Münstermann, Sebastian (steel research international)
Resistance spot‐welded joints containing press‐hardened steels are seen to exhibit a fracture mode called total dome failure, where the weld nugget completely separates from one steel sheet along the weld nugget edge. The effect of weld nugget shape and material property gradients is studied based on damage mechanics modeling and experimental validation to shed light on the underlying influencing factors. For a three‐steel‐sheet spot‐welded joint combining DP600 (1.5 mm)–CR1900T (1.0 mm)–CR1900T (1.0 mm), experiments under shear loading reveal that fracture occurs in the DP600 sheet along the weld nugget edge. In subsequent numerical simulation studies with damage mechanics models whose parameters are independently calibrated for every involved material configuration, three variations of the geometrical joint configuration are considered—an approximation of the real joint, one variation with a steeper weld nugget shape, and one variation with a less pronounced gradient between weld nugget material and heat‐affected zone material properties. The results of the finite‐element simulations show that a shallower weld nugget and a more pronounced material gradient lead to a faster increase of plastic strain at the edge of the weld nugget and promote the occurrence of total dome failure.
Keywords: Materials Chemistry; Metals and Alloys; Physical and Theoretical Chemistry; Condensed Matter Physics

Anisotropic Mechanical and Microstructural Properties of a Ti-6Al-7Nb Alloy for Biomedical Applications Manufactured via Laser Powder Bed Fusion - Milaege, Dennis; Eschemann, Niklas; Hoyer, Kay-Peter; Schaper, Mirko (Crystals)
Through tailoring the geometry and design of biomaterials, additive manufacturing is revolutionizing the production of metallic patient-specific implants, e.g., the Ti-6Al-7Nb alloy. Unfortunately, studies investigating this alloy showed that additively produced samples exhibit anisotropic microstructures. This anisotropy compromises the mechanical properties and complicates the loading state in the implant. Moreover, the minimum requirements as specified per designated standards such as ISO 5832-11 are not met. The remedy to this problem is performing a conventional heat treatment. As this route requires energy, infrastructure, labor, and expertise, which in turn mean time and money, many of the additive manufacturing benefits are negated. Thus, the goal of this work was to achieve better isotropy by applying only adapted additive manufacturing process parameters, specifically focusing on the build orientations. In this work, samples orientated in 90°, 45°, and 0° directions relative to the building platform were manufactured and tested. These tests included mechanical (tensile and fatigue tests) as well as microstructural analyses (SEM and EBSD). Subsequently, the results of these tests such as fractography were correlated with the acquired mechanical properties. These showed that 90°-aligned samples performed best under fatigue load and that all requirements specified by the standard regarding monotonic load were met.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Electrochemical Removal of HF from Carbonate-based LiPF6-containing Li-ion Battery Electrolytes - Ge, Xiaokun; Huck, Marten; Kuhlmann, Andreas; Tiemann, Michael; Weinberger, Christian; Xu, Xiaodan; Zhao, Zhenyu; Steinrueck, Hans-Georg (Journal of The Electrochemical Society)
Due to the hydrolytic instability of LiPF6 in carbonate-based solvents, HF is a typical impurity in Li-ion battery electrolytes. HF significantly influences the performance of Li-ion batteries, for example by impacting the formation of the solid electrolyte interphase at the anode and by affecting transition metal dissolution at the cathode. Additionally, HF complicates studying fundamental interfacial electrochemistry of Li-ion battery electrolytes, such as direct anion reduction, because it is electrocatalytically relatively unstable, resulting in LiF passivation layers. Methods to selectively remove ppm levels of HF from LiPF6-containing carbonate-based electrolytes are limited. We introduce and benchmark a simple yet efficient electrochemical in situ method to selectively remove ppm amounts of HF from LiPF6-containing carbonate-based electrolytes. The basic idea is the application of a suitable potential to a high surface-area metallic electrode upon which only HF reacts (electrocatalytically) while all other electrolyte components are unaffected under the respective conditions.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Cold denaturation of DNA origami nanostructures - Dornbusch, Daniel; Hanke, Marcel; Tomm, Emilia; Kielar, Charlotte; Grundmeier, Guido; Keller, Adrian; Fahmy, Karim (Chemical Communications)
The coupling of structural transitions to heat capacity changes leads to destabilization of macromolecules at both, elevated and lowered temperatures. DNA origami not only exhibit this property but also provide...
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Frustrated Lewis Pair Catalysed Reactions - Zhou, Rundong; Tavandashti, Zoleykha; Paradies, Jan (SynOpen)
In recent years, frustrated Lewis pairs have been widely used in small molecules activation and catalytic transformations. This graphic review is aimed to provide the fundamental understanding of frustrated Lewis pair reactivity and the exploitation thereof in catalytic reactions.
Keywords: Organic Chemistry; Materials Science (miscellaneous); Biomaterials; Catalysis

Nonlinear Dielectric Nanoresonators and Metasurfaces: Toward Efficient Generation of Entangled Photons - Sharapova, Polina R.; Kruk, Sergey S.; Solntsev, Alexander S. (Laser & Photonics Reviews)
Keywords: Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Development of a numerical simulation model for self-piercing riveting of additive manufactured AlSi10Mg - Heyser, Per; Petker, Rudolf; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
Laser additive manufacturing processes are used for the production of highly complex geometric structures due to their high geometric freedom. Additive manufacturing processes, in particular powder-based selective laser melting, are used to produce metallic additive manufactured components for the automotive and aerospace industries. Different materials are often joined together to realize sustainable lightweight construction. The production of such mixed construction joints is often realized using mechanical joining technology (e.g. self-piercing riveting). However, there is currently very little experience with the mechanical joining of metallic additive manufacturing components. Furthermore, there is insufficient knowledge about the effects that occur during the mechanical joining of additive manufacturing components. In this article, a method is presented to investigate the joinability of additively manufactured components with conventionally manufactured components using a numerical simulation of the self-piercing riveting process. For this purpose, the additive manufacturing materials are characterized experimentally, the simulation model is configured, and the joining process with additive manufacturing materials is represented in the numerical simulation. Furthermore, the influence of the building direction on the mechanical properties is shown using miniature tensile specimens. Besides the configuration of the simulation model, the influence of heat treatment on the self-piercing riveting process is presented.
Keywords: Mechanical Engineering; General Materials Science

Characterizing Ion Transport in Electrolytes via Concentration and Velocity Profiles - Mistry, Aashutosh; Srinivasan, Venkat; Steinrück, Hans-Georg (Advanced Energy Materials)
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment

Correction: Thermal influence of resistance spot welding on a nearby overmolded thermoplastic–metal joint - Wippermann, Jan; Meschut, Gerson; Koshukow, Wikentij; Liebsch, Alexander; Gude, Maik; Minch, Steven; Kolbe, Björn (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Application of a new strategy for time-efficient laser treatment of galvanized steel substrates to improve the adhesion properties - Voswinkel, Dietrich (Journal of Manufacturing Processes)
Laser structuring to improve the adhesion properties of steel substrates in fiber-metal laminates offers many advantages that are highly suitable for modern industrial requirements. Maintenance and energy costs are relatively low, it is easy to automate, and there are no by-products such as chemicals or abrasives to dispose of or recycle. This makes laser structuring a particularly environmentally friendly process, which is nowadays more important than ever. On the other hand, the process time for laser structuring is much higher than for chemical pre-treatment, for example. In past studies, the time and cost efficiency of the laser structuring process has tended to play a minor role. However, there are approaches in which laser structured surfaces are adapted to the shear stress peaks occurring within the adhesive layer, thus requiring only partial structuring of the area to be bonded, potentially saving process time. In this experimental study, electrolytically galvanized steel substrates were partially laser structured to match the shear stress distribution and then bonded to a carbon fiber-reinforced plastic. The adhesion properties achieved were characterized using shear tensile tests and compared with the properties of the fully structured ones. With the partial laser structuring, a saving of 66 % of the conventional process time was achieved while maintaining 95 % of the same shear strength.
Keywords: Laser treatment Adhesive bonding Surface technology Hybrid materials

Realization of a Multi-Output Quantum Pulse Gate for Decoding High-Dimensional Temporal Modes of Single-Photon States - Serino, Laura; Gil López, Jano; Stefszky, Michael; Ricken, Raimund; Eigner, Christof; Brecht, Benjamin; Silberhorn, Christine (PRX Quantum)
Keywords: General Physics and Astronomy; Mathematical Physics; Applied Mathematics; Electronic; Optical and Magnetic Materials; Electrical and Electronic Engineering; General Computer Science

Morphological and mechanical properties of foamed thick-walled Wood-Plastic-Composite structures - Moritzer, Elmar; Flachmann, Felix (Journal of Cellular Plastics)
Microcellular wood fiber reinforced polymers offer the possibility to reduce the use of fossil raw materials. In particular, thick-walled structures with thicknesses greater than 6 mm offer a high potential for weight savings. This study investigates the cell structures and mechanical properties of injection-molded test specimens. The influence of different thicknesses (6–10 mm) along with different chemical blowing agents (endothermic, exothermic) with varying dosages (0–2 wt%) is analyzed. The investigations reveal that exothermic chemical blowing agents form finer cells consistently to thin-walled structures than endothermic ones. Higher foaming agent content leads to higher pore fractions, with many small cells coalescing into a large open-pore cell network. The mechanical properties depend mainly on the pore content of the sample. The specific tensile properties deteriorate with the use of chemical blowing agents (CFA), whereas the sandwich structure produced with compact edge layers has a positive influence on the specific flexural properties.
Keywords: Materials Chemistry; Polymers and Plastics; General Chemistry

Development of an adaptive coaxial concrete rheometer and rheological characterisation of fresh concrete - Josch, Sebastian; Jesinghausen, Steffen; Schmid, Hans-Joachim (Applied Rheology)
Abstract The accessibility to rheological parameters for concrete is becoming more and more relevant. This is mainly related to the constantly emerging challenges, such as not only the development of high-strength concretes is progressing very fast but also the simulation of the flow behaviour is of high importance. The main problem, however, is that the rheological characterisation of fresh concrete is not possible via commercial rheometers. The so-called concrete rheometers provide valuable relative values for comparing different concretes, but they cannot measure absolute values. Therefore, we developed an adaptive coaxial concrete rheometer (ACCR) that allows the measurement of fresh concrete with particles up to d max = 5.5 mm {d}_{{\rm{\max }}}=5.5\hspace{.5em}{\rm{mm}} . The comparison of the ACCR with a commercial rheometer showed very good agreement for selected test materials (Newtonian fluid, shear thinning fluid, suspension, and yield stress fluid), so that self-compacting concrete was subsequently measured. Since these measurements showed a very high reproducibility, the rheological properties of the fresh concrete could be determined with high accuracy. The common flow models (Bingham (B), Herschel–Bulkley, modified Bingham (MB) models) were also tested for their applicability, with the Bingham and the modified Bingham model proving to be the best suitable ones.
Keywords: Condensed Matter Physics; General Materials Science

Thermal influence of resistance spot welding on a nearby overmolded thermoplastic–metal joint - Wippermann, Jan; Meschut, Gerson; Koschukow, Wikentji; Liebsch, Alexander; Gude, Maik; Minch, Steven; Kolbe, Björn (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Understanding the Redox Mechanism of Sulfurized Poly(acrylonitrile) as Highly Rate and Cycle Stable Cathode Material for Sodium-Sulfur Batteries - Kappler, Julian; Tonbul, Güldeniz; Schoch, Roland; Murugan, Saravanakumar; Nowakowski, Michał; Lange, Pia Lena; Klostermann, Sina Vanessa; Bauer, Matthias; Schleid, Thomas; Kästner, Johannes; Buchmeiser, Michael Rudolf (Journal of The Electrochemical Society)
Room temperature sodium-sulfur (RT Na-S) batteries are considered potential candidates for stationary power storage applications due to their low cost, broad active material availability and low toxicity. Challenges, such as high volume expansion of the S-cathode upon discharge, low electronic conductivity of S as active material and herewith limited rate capability as well as the shuttling of polysulfides (PSs) as intermediates often impede the cycle stability and practical application of Na-S batteries. Sulfurized poly(acrylonitrile) (SPAN) inherently inhibits the shuttling of PSs and shows compatibility with carbonate-based electrolytes, however, its exact redox mechanism remained unclear to date. Herein, we implement a commercially available and simple electrolyte into the Na-SPAN cell chemistry and demonstrate its high rate and cycle stability. Through the application of in situ techniques utilizing electronic impedance spectroscopy (EIS) and X-ray absorption spectroscopy (XAS) at different depths of charge and discharge, an insight into SPAN’s redox chemistry is obtained.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Large-Scale Formation of DNA Origami Lattices on Silicon - Tapio, Kosti; Kielar, Charlotte; Parikka, Johannes M.; Keller, Adrian; Järvinen, Heini; Fahmy, Karim; Toppari, J. Jussi (Chemistry of Materials)
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

Stability of DNA Origami Nanostructures in Physiological Media: The Role of Molecular Interactions - Linko, Veikko; Keller, Adrian (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Compact Metasurface-Based Optical Pulse-Shaping Device - Geromel, René; Georgi, Philip; Protte, Maximilian; Lei, Shiwei; Bartley, Tim; Huang, Lingling; Zentgraf, Thomas (Nano Letters)
Dispersion is present in every optical setup and is often an undesired effect, especially in nonlinear-optical experiments where ultrashort laser pulses are needed. Typically, bulky pulse compressors consisting of gratings or prisms are used to address this issue by precompensating the dispersion of the optical components. However, these devices are only able to compensate for a part of the dispersion (second-order dispersion). Here, we present a compact pulse-shaping device that uses plasmonic metasurfaces to apply an arbitrarily designed spectral phase delay allowing for a full dispersion control. Furthermore, with specific phase encodings, this device can be used to temporally reshape the incident laser pulses into more complex pulse forms such as a double pulse. We verify the performance of our device by using an SHG-FROG measurement setup together with a retrieval algorithm to extract the dispersion that our device applies to an incident laser pulse.
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Comparative Study of the Influence of Heat Treatment and Additive Manufacturing Process (LMD & L-PBF) on the Mechanical Properties of Specimens Manufactured from 1.2709 - Gnaase, Stefan; Niggemeyer, Dennis; Lehnert, Dennis; Bödger, Christian; Tröster, Thomas (Crystals)
(1) This work answers the question of whether and to what extent there is a significant difference in mechanical properties when different additive manufacturing processes are applied to the material 1.2709. The Laser-Powder-Bed-Fusion (L-PBF) and Laser-Metal-Deposition (LMD) processes are considered, as they differ fundamentally in the way a part is manufactured. (2) Known process parameters for low-porosity parts were used to fabricate tensile strength specimens. Half of the specimens were heat-treated, and all specimens were tested for mechanical properties in a quasi-static tensile test. In addition, the material hardness was determined. (3) It was found that, firstly, heat treatment resulted in a sharp increase in mechanical properties such as hardness, elastic modulus, yield strength and ultimate strength. In addition to the increase in these properties, the elongation at break also decreases significantly after heat treatment. The choice of process, on the other hand, does not give either process a clear advantage in terms of mechanical properties but shows that it is necessary to consider the essential mechanical properties for a desired application.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

A Pulsed Lidar System With Ultimate Quantum Range Accuracy - Kruse, Stephan; Serino, Laura; Folge, Patrick Fabian; Echeverria Oviedo, Dana; Bhattacharjee, Abhinandan; Stefszky, Michael; Scheytt, J. Christoph; Brecht, Benjamin; Silberhorn, Christine (IEEE Photonics Technology Letters)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Integrating Prospective LCA in the Development of Automotive Components - Grenz, Julian; Ostermann, Moritz; Käsewieter, Karoline; Cerdas, Felipe; Marten, Thorsten; Herrmann, Christoph; Tröster, Thomas (Sustainability)
The development of automotive components with reduced greenhouse gas (GHG) emissions is needed to reduce overall vehicle emissions. Life Cycle Engineering (LCE) based on Life Cycle Assessment (LCA) supports this by providing holistic information and improvement potentials regarding eco-efficient products. Key factors influencing LCAs of automotive components, such as material production, will change in the future. First approaches for integrating future scenarios for these key factors into LCE already exist, but they only consider a limited number of parameters and scenarios. This work aims to develop a method that can be practically applied in the industry for integrating prospective LCAs (pLCA) into the LCE of automotive components, considering relevant parameters and consistent scenarios. Therefore, pLCA methods are further developed to investigate the influence of future scenarios on the GHG emissions of automotive components. The practical application is demonstrated for a vehicle component with different design options. This paper shows that different development paths of the foreground and background system can shift the ecological optimum of design alternatives. Therefore, future pathways of relevant parameters must be considered comprehensively to reduce GHG emissions of future vehicles. This work contributes to the methodological and practical integration of pLCA into automotive development processes and provides quantitative results.
Keywords: prospective LCA; life cycle engineering (LCE); lightweight design; automotive components; body parts; circular economy; steel; aluminum; hybrid materials; fiber metal laminates

Engineering Sub‐Nanometer Hafnia‐Based Ferroelectric to Break The Scaling Relation for High‐Efficiency Piezocatalytic Water Splitting - Su, Ran; Zhang, Jiahui; Wong, Vienna; Zhang, Dawei; Yang, Yong; Luo, Zheng‐Dong; Wang, Xiaojing; Wen, Hui; Liu, Yang; Seidel, Jan; Yang, Xiaolong; Pan, Ying; et al. (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Cation-dependent assembly of hexagonal DNA origami lattices on SiO2 surfaces - Pothineni, Bhanu Kiran; Grundmeier, Guido; Keller, Adrian (Nanoscale)
DNA origami nanostructures have emerged as functional materials for applications in various areas of science and technology. In particular, the transfer of the DNA origami shape into inorganic materials using...
Keywords: General Materials Science

Remote Epitaxy of Cubic Gallium Nitride on Graphene‐Covered 3C‐SiC Substrates by Plasma‐Assisted Molecular Beam Epitaxy - Littmann, Mario; Reuter, Dirk; As, Donat Josef (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Steady-State Error Compensation for Reinforcement Learning-Based Control of Power Electronic Systems - Weber, Daniel; Schenke, Maximilian; Wallscheid, Oliver (IEEE Access)
Keywords: General Engineering; General Materials Science; General Computer Science; Electrical and Electronic Engineering

Modeling of Masked Droplet Deposition for Site-Controlled Ga Droplets - Feddersen, Stefan; Zolatanosha, Viktoryia; Alshaikh, Ahmed; Reuter, Dirk; Heyn, Christian (Nanomaterials)
Site-controlled Ga droplets on AlGaAs substrates are fabricated using area-selective deposition of Ga through apertures in a mask during molecular beam epitaxy (MBE). The Ga droplets can be crystallized into GaAs quantum dots using a crystallization step under As flux. In order to model the complex process, including the masked deposition of the droplets and a reduction of their number during a thermal annealing step, a multiscale kinetic Monte Carlo (mkMC) simulation of self-assembled Ga droplet formation on AlGaAs is expanded for area-selective deposition. The simulation has only two free model parameters: the activation energy for surface diffusion and the activation energy for thermal escape of adatoms from a droplet. Simulated droplet numbers within the opening of the aperture agree quantitatively with the experimental results down to the perfect site-control, with one droplet per aperture. However, the model parameters are different compared to those of the self-assembled droplet growth. We attribute this to the presence of the mask in close proximity to the surface, which modifies the local process temperature and the As background. This approach also explains the dependence of the model parameters on the size of the aperture.
Keywords: General Materials Science; General Chemical Engineering

UV-enhanced environmental charge compensation in near ambient pressure XPS - Müller, Hendrik; Weinberger, Christian; Grundmeier, Guido; de los Arcos de Pedro, Maria Teresa (Journal of Electron Spectroscopy and Related Phenomena)
Keywords: Physical and Theoretical Chemistry; Spectroscopy; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Radiation; Electronic; Optical and Magnetic Materials

An Experimental and Computational Modeling Study on Additively Manufactured Micro‐Architectured Ti–24Nb–4Zr–8Sn Hollow‐Strut Lattice Structures - Pramanik, Sudipta; Milaege, Dennis; Hein, Maxwell; Andreiev, Anatolii; Schaper, Mirko; Hoyer, Kay-Peter (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

NELLIE: Never-Ending Linking for Linked Open Data - Ahmed, Abdullah Fathi; Sherif, Mohamed Ahmed; Ngomo, Axel-Cyrille Ngonga (IEEE Access)
Keywords: General Engineering; General Materials Science; General Computer Science; Electrical and Electronic Engineering

Overcoming the Miscibility Gap of GaN/InN in MBE Growth of Cubic InxGa1–xN - Zscherp, Mario Fabian; Jentsch, Silas Aurel; Müller, Marius Johannes; Lider, Vitalii; Becker, Celina; Chen, Limei; Littmann, Mario; Meier, Falco; Beyer, Andreas; Hofmann, Detlev Michael; As, Donat Josef; Klar, Peter Jens; et al. (ACS Applied Materials & Interfaces)
Keywords: General Materials Science

Investigations on the Influences of the Thermomechanical Manufacturing of Aluminium Auxiliary Joining Elements - Borgert, Thomas; Henke, Maximilian; Homberg, Werner (Journal of Manufacturing and Materials Processing)
The demands on joining technology are constantly increasing due to the consistent lightweight construction and the associated increasing material mix. To meet these requirements, the adaptability of the joining processes must be improved to be able to process different material combinations and to react to challenges caused by deviations in the process chain. One example of a highly adaptable process due to the two-step process sequence is thermomechanical joining with Friction Spun Joint Connectors (FSJCs) that can be individually adapted to the joint. In this paper, the potentials of the adaption in the two-stage joining process with aluminium auxiliary joining elements are investigated. To this end, it is first investigated whether a thermomechanical forming process can be used to achieve a uniform and controlled manufacturing regarding the process variable of the temperature as well as the geometry of the FSJC. Based on the successful proof of the high and good repeatability in the FSJC manufacturing, possibilities, and potentials for the targeted influencing of the process and FSJC geometry are shown, based on an extensive variation of the process input variables (delivery condition and thus mechanical properties of the raw parts as well as the process parameters of rotational speed and feed rate). Here it can be shown that above all, the feed rate of the final forming process has the strongest influence on the process and thus also offers the strongest possibilities for influencing it.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Structural transitions during Ni nanoparticle formation by decomposition of a Ni-containing metal-organic framework using in-situ total scattering - Prinz, Nils; Strübbe, Sven; Bauer, Matthias; Zobel, Mirijam (New Journal of Chemistry)
For improved and rational design of catalysts, in-depth knowledge of their formation and structural evolution during synthesis is a key parameter. Thus, preparation of a Ni methanation catalyst derived from...
Keywords: Materials Chemistry; General Chemistry; Catalysis

Quasi-In Situ Localized Corrosion of an Additively Manufactured FeCo Alloy in 5 Wt Pct NaCl Solution - Pramanik, Sudipta; Krüger, Jan Tobias; Schaper, Mirko; Hoyer, Kay-Peter (Metallurgical and Materials Transactions A)
Abstract FeCo alloys are important materials used in pumps and motors in the offshore oil and gas drilling industry. These alloys are subjected to marine environments with a high NaCl concentration, therefore, corrosion and catastrophic failure are anticipated. So, the surface dissolution of additively manufactured FeCo samples is investigated in a quasi- in situ manner, in particular, the pitting corrosion in 5.0 wt pct NaCl solution. The local dissolution of the same sample region is monitored after 24, 72, and 168 hours. Here, the formation of rectangular and circular pits of ultra-fine dimensions (less than 0.5 µ m) is observed with increasing immersion time. In addition, the formation of a corrosion-inhibiting surface layer is detected on the sample surface. Surface dissolution leads to a change in the surface structure, however, no change in grain shape or grain size is noticed. The surface topography after local dissolution is correlated to the grain orientation. Quasi- in situ analysis shows the preferential dissolution of high-angle grain boundaries (HAGBs) leading to a change in the fraction of HAGBs and low-angle grain boundaries fraction (LAGBs). For the FeCo sample, a potentiodynamic polarisation test reveals a corrosion potential (E corr ) of − 0.475 V referred to the standard hydrogen electrode (SHE) and a corrosion exchange current density (i corr ) of 0.0848 A/m 2 . Furthermore, quasi- in situ experiments showed that grains oriented along certain crystallographic directions are corroding more compared to other grains leading to a significant decrease in the local surface height. Grains with a plane normal close to the $$\langle {1}00\rangle$$ ⟨ 100 ⟩ direction reveal lower surface dissolution and higher corrosion resistance, whereas planes normal close to the $$\langle {11}0\rangle$$ ⟨ 110 ⟩ direction and the $$\langle {111}\rangle$$ ⟨ 111 ⟩ direction exhibit a higher surface dissolution.
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics

Adhesion properties of the hybrid system made of laser-structured aluminium EN AW 6082 and CFRP by co-bonding-pressing process - Wu, Shuang; Delp, Alexander; Freund, Jonathan; Walther, Frank; Haubrich, Jan; Löbbecke, Miriam; Tröster, Thomas (The Journal of Adhesion)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanics of Materials; General Chemistry

Relationship between laser-generated micro- and nanostructures and the long-term stability of bonded epoxy-aluminum joints - Freund, Jonathan; Löbbecke, Miriam; Delp, Alexander; Walther, Frank; Wu, Shuang; Tröster, Thomas; Haubrich, Jan (The Journal of Adhesion)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanics of Materials; General Chemistry

Superstructure-dependent stability of DNA origami nanostructures in the presence of chaotropic denaturants - Hanke, Marcel; Dornbusch, Daniel; Tomm, Emilia; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian (Nanoscale)
The structural stability of DNA origami nanostructures in various chemical environments is an important factor in numerous applications, ranging from biomedicine and biophysics to analytical chemistry and materials synthesis. In...
Keywords: General Materials Science

Potentials of a friction-induced recycling process to improve resource and energy efficiency in manufacturing technology - Borgert, Thomas; Milaege, Dennis; Schweizer, Swetlana; Homberg, Werner; Schaper, Mirko; Tröster, Thomas (International Journal of Material Forming)
Abstract Efforts to enhance sustainability in all areas of life are increasing worldwide. In the field of manufacturing technology, a wide variety of approaches are being used to improve both resource and energy efficiency. Efficiency as well as sustainability can be improved by creating a circular economy or through energy-efficient recycling processes. As part of the interdisciplinary research group "Light—Efficient—Mobile" investigations on the energy-efficient friction-induced recycling process have been carried out at the department of Forming and Machining Technology at Paderborn University. E.g. using the friction-induced recycling process, different formless solid aluminum materials can be direct recycled into semi-finished products in an energy-efficient manner. The results of investigations with regard to the influence of the geometrical shape and filling rate of the aluminum particles to be recycled as well as the rotational speed of the continuously rotating wheel are explained in this paper. In addition to the recycling of aluminum chips, aluminum particles like powders from the field of additive manufacturing are processed. Based on these results, the future potentials of solid-state recycling processes and their contribution to the circular economy are discussed. The main focus here is on future interdisciplinary research projects to achieve circularity in the manufacturing of user-individual semi-finished products as well as the possibility to selectively adjust the product properties with the continuous recycling process.
Keywords: General Materials Science

Impact of 3D Curvature on the Polarization Orientation in Non-Ising Domain Walls - Acevedo-Salas, Ulises; Croes, Boris; Zhang, Yide; Cregut, Olivier; Dorkenoo, Kokou Dodzi; Kirbus, Benjamin; Singh, Ekta; Beccard, Henrik; Rüsing, Michael; Eng, Lukas M.; Hertel, Riccardo; Eliseev, Eugene A.; et al. (Nano Letters)
Ferroelectric domain boundaries are quasi-two-dimensional functional interfaces with high prospects for nanoelectronic applications. Despite their reduced dimensionality, they can exhibit complex non-Ising polarization configurations and unexpected physical properties. Here, the impact of the three-dimensional (3D) curvature on the polarization profile of nominally uncharged 180° domain walls in LiNbO3 is studied using second-harmonic generation microscopy and 3D polarimetry analysis. Correlations between the domain-wall curvature and the variation of its internal polarization unfold in the form of modulations of the Néel-like character, which we attribute to the flexoelectric effect. While the Néel-like character originates mainly from the tilting of the domain wall, the internal polarization adjusts its orientation due to the synergetic upshot of dipolar and monopolar bound charges and their variation with the 3D curvature. Our results show that curved interfaces in solid crystals may offer a rich playground for tailoring nanoscale polar states.
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Vibrational properties of LiNbO3 and LiTaO3 under uniaxial stress - Singh, Ekta; Pionteck, Mike N.; Reitzig, Sven; Lange, Michael; Rüsing, Michael; Eng, Lukas M.; Sanna, Simone (Physical Review Materials)
Structural strain severely impacts material properties, such as the linear and nonlinear optical response. Moreover, strain plays a key role, e.g., in the physics of ferroelectrics and, in particular, of their domain walls. μ-Raman spectroscopy is a well-suited technique for the investigation of such strain effects as it allows to measure the lattice dynamics locally. However, quantifying and reconstructing strain fields from Raman maps requires knowledge on the strain dependence of phonon frequencies. In this paper, we have analyzed both theoretically and experimentally the phonon frequencies in the widely used ferroelectrics lithium niobate and lithium tantalate as a function of uniaxial strain via density functional theory and μ-Raman spectroscopy. Overall, we find a good agreement between our ab initio models and the experimental data performed with a stress cell. The majority of phonons show an increase in frequency under compressive strain, whereas the opposite is observed for tensile strains. Moreover, for E-type phonons, we observe the lifting of degeneracy already at moderate strain fields (i.e., at ±0.2%) along the x and y directions. This paper, hence, allows for the systematic analysis of three-dimensional strains in modern-type bulk and thin-film devices assembled from lithium niobate and tantalate.
Keywords: Physics and Astronomy (miscellaneous); General Materials Science

Thermophoretic Analysis of Biomolecules across the Nanoscales in Self-Assembled Polymeric Matrices - Liu, Ping; Schumann, Nils; Abele, Fabian; Ren, Fazheng; Hanke, Marcel; Xin, Yang; Hartmann, Andreas; Schlierf, Michael; Keller, Adrian; Lin, Weilin; Zhang, Yixin (ACS Applied Nano Materials)
Keywords: General Materials Science

Vibrational Properties of the Potassium Titanyl Phosphate Crystal Family - Neufeld, Sergej; Gerstmann, Uwe; Padberg, Laura; Eigner, Christof; Berth, Gerhard; Silberhorn, Christine; Eng, Lukas M.; Schmidt, Wolf Gero; Rüsing, Michael (Crystals)
The crystal family of potassium titanyl phosphate (KTiOPO4) is a promising material group for applications in quantum and nonlinear optics. The fabrication of low-loss optical waveguides, as well as high-grade periodically poled ferroelectric domain structures, requires a profound understanding of the material properties and crystal structure. In this regard, Raman spectroscopy offers the possibility to study and visualize domain structures, strain, defects, and the local stoichiometry, which are all factors impacting device performance. However, the accurate interpretation of Raman spectra and their changes with respect to extrinsic and intrinsic defects requires a thorough assignment of the Raman modes to their respective crystal features, which to date is only partly conducted based on phenomenological modelling. To address this issue, we calculated the phonon spectra of potassium titanyl phosphate and the related compounds rubidium titanyl phosphate (RbTiOPO4) and potassium titanyl arsenate (KTiOAsO4) based on density functional theory and compared them with experimental data. Overall, this allows us to assign various spectral features to eigenmodes of lattice substructures with improved detail compared to previous assignments. Nevertheless, the analysis also shows that not all features of the spectra can unambigiously be explained yet. A possible explanation might be that defects or long range fields not included in the modeling play a crucial rule for the resulting Raman spectrum. In conclusion, this work provides an improved foundation into the vibrational properties in the KTiOPO4 material family.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Solid solutions of lithium niobate and lithium tantalate: crystal growth and the ferroelectric transition - Bashir, Umar; Böttcher, Klaus; Klimm, Detlef; Ganschow, Steffen; Bernhardt, Felix; Sanna, Simone; Rüsing, Michael; Eng, Lukas M.; Bickermann, Matthias (Ferroelectrics)
Specific heat capacity measurements by differential scanning calorimetry (DSC) of single crystals of solid solutions of LiNbO3 and LiTaO3 are reported and compared with corresponding ab initio calculations, with the aim to investigate the variation of the ferroelectric Curie temperature as a function of composition. For this purpose, single crystals of these solid solutions were grown with Czochralski pulling along the c-axis. Elemental composition of Nb and Ta was investigated using XRF analysis, and small samples with homogeneous and well known composition were used for the DSC measurements. We observed that the ferroelectric Curie temperature decreases linearly with increasing Ta concentration in the LiNb1−x Tax O3 solid solution crystals. Furthermore, the ferroelectric transition width of a mixed crystal appears to be smaller, as compared to pure LiTaO3.
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Increased Sustainability in Fastener Production with the Example of Self-Piercing Rivets - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Journal of Manufacturing and Materials Processing)
The sustainability of the manufacturing industry is of special importance to increase the protection of the environment. The production of fasteners like self-piercing rivets, however, is costly, time-consuming and energy-intensive. The heat treatment and the coating, which are mandatory in conventional self-piercing rivets to achieve adequate strength, ductility and corrosion resistance, are especially crucial in this respect. Within this paper, an approach for an increase in the sustainability in fastener production is presented. The use of alternative, high strain hardening stainless steels as rivet material enables a shortening of the process chain, because post treatment of the rivets after they are formed can be omitted. As the change in rivet material and processing causes some issues along the process chain, the focus of this paper is on the holistic evaluation of the challenges within the forming of high strain hardening steel and the impact of the changed rivet properties on the joining result.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

On the accuracy, stability and computational efficiency of explicit last-stage diagonally implicit Runge–Kutta methods (ELDIRK) for the adaptive solution of phase-field problems - Westermann, Hendrik; Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Multiphase elasto-plastic mean-field homogenisation and its consistent linearisation - Lenz, Peter; Kreutzheide, Phil; Mahnken, Rolf (Computers & Structures)
Keywords: Computer Science Applications; Mechanical Engineering; General Materials Science; Modeling and Simulation; Civil and Structural Engineering